2004
DOI: 10.1038/sj.eye.6700541
|View full text |Cite
|
Sign up to set email alerts
|

Association of binocular lower visual field impairment, impaired simultaneous perception, disordered visually guided motion and inaccurate saccades in children with cerebral visual dysfunction—a retrospective observational study

Abstract: The principal pathways serving higher visual function comprise the dorsal stream and the ventral stream. The dorsal stream runs between the occipital lobes and the parietal lobes and subserves the ability to process the whole visual scene and carry out visually guided movement. The ventral stream runs between the occipital lobes and temporal lobe tissue and primarily subserves visual recognition and memory. These tissues are susceptible to dysfunction in children with brain damage. We report a series of 40 chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 10 publications
2
73
2
Order By: Relevance
“…The dorsal pathway extends between the occipital and parietal lobes. 2 Its structures are involved in motion perception, stereopsis, spatial vision, and visuospatial attention (vision for action), plus the ability to extract visual data from a complex visual scene.…”
Section: Discussionmentioning
confidence: 99%
“…The dorsal pathway extends between the occipital and parietal lobes. 2 Its structures are involved in motion perception, stereopsis, spatial vision, and visuospatial attention (vision for action), plus the ability to extract visual data from a complex visual scene.…”
Section: Discussionmentioning
confidence: 99%
“…351 Selective dorsal stream dysfunction correlates with the finding that PVL shows a predilection for involving the lower visual fields. 141,142,283 These findings could be explained by bilateral injury to the superior striate or extrastriate cortex. Galetta and Grossman found that horizontal meridian corresponds to the base of the calcarine fissures, 186 which lie adjacent to the lesions of PVL.…”
Section: Dorsal and Ventral Stream Dysfunctionmentioning
confidence: 95%
“…Children with PVL often display evidence of selective dorsal stream dysfunction, which selectively affects visuocognitive functions such as spatial awareness, attention, and visually-guided motion. 21,139,140,141,397,398,509 Affected children may have difficulty distinguishing a line on the ground from a step, have difficulty combining tasks such as writing and listening, get frustrated if distracted while engaging in another activity, have difficulty choosing a toy in a toy box or against a cluttered background, get lost in the crowded visual scenes, and have difficulty walking down stairs or on uneven ground. These symptoms can sometimes be found even when MR imaging shows no evidence of periventricular leukomalacia or other abnormalities.…”
Section: Dorsal and Ventral Stream Dysfunctionmentioning
confidence: 99%
“…Even more challenging are the children, who present with normal or slightly reduced acuities but with significant cognitive visual dysfunction. 31,46 These children are often misdiagnosed or even ignored because of the apparent contradictory findings of little or no visual acuity and field loss in the presence of significant and often ill-understood visual complaints. The associative visual cortex areas contribute a significant portion of the visual disability in a number of children with brain damage and visual disability.…”
Section: Associative Visual Cortex Areasmentioning
confidence: 99%